2017
DOI: 10.1038/s41467-017-01466-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-space and real-time dynamics of CRISPR-Cas9 visualized by high-speed atomic force microscopy

Abstract: The CRISPR-associated endonuclease Cas9 binds to a guide RNA and cleaves double-stranded DNA with a sequence complementary to the RNA guide. The Cas9–RNA system has been harnessed for numerous applications, such as genome editing. Here we use high-speed atomic force microscopy (HS-AFM) to visualize the real-space and real-time dynamics of CRISPR-Cas9 in action. HS-AFM movies indicate that, whereas apo-Cas9 adopts unexpected flexible conformations, Cas9–RNA forms a stable bilobed structure and interrogates targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
200
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(213 citation statements)
references
References 31 publications
13
200
0
Order By: Relevance
“…In the studies by Dagdas et al and Chen et al , most of the S355C–S867C molecules exhibited ~1.0 FRET efficiency, suggesting that the HNH domain in almost all of the Cas9 molecules adopts the cleavage‐competent (D) position. In contrast, in the studies by us and Yang et al , the major peak value of the FRET efficiency was ~0.4, suggesting that the HNH domain is predominantly located in the intermediate (I) position, consistent with the recent HS‐AFM observation (Shibata et al , ). In addition, the studies by us and Yang et al demonstrated the existence of the pre‐cleavage (D*) HNH position.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the studies by Dagdas et al and Chen et al , most of the S355C–S867C molecules exhibited ~1.0 FRET efficiency, suggesting that the HNH domain in almost all of the Cas9 molecules adopts the cleavage‐competent (D) position. In contrast, in the studies by us and Yang et al , the major peak value of the FRET efficiency was ~0.4, suggesting that the HNH domain is predominantly located in the intermediate (I) position, consistent with the recent HS‐AFM observation (Shibata et al , ). In addition, the studies by us and Yang et al demonstrated the existence of the pre‐cleavage (D*) HNH position.…”
Section: Discussionsupporting
confidence: 83%
“…Our smFRET data revealed the fluctuations between the REC and NUC lobes in apo‐Cas9 (Fig ), indicating that, in addition to the static closed conformation, apo‐Cas9 adopts transient conformations. Consistent with this, a single‐molecule study using high‐speed atomic force microscopy (HS‐AFM) visualized highly flexible conformations of apo‐Cas9 (Shibata et al , ). The movement of the REC lobe relative to the NUC lobe can provide interaction interfaces for the sgRNA; thus, the flexible movement in apo‐Cas9 may play an important role in the assembly with the sgRNA.…”
Section: Discussionmentioning
confidence: 79%
“…5F). It has been shown that Cas9 can remain bound to the DNA after cleavage for an extended time [33][34][35] and it preferentially releases the PAM-distal, non-target strand 36 . Our data suggests that this property might result in an asymmetrical influence of the bound Cas9/gRNA complex on the HDR process, and that perhaps the released PAM-distal, non-target strand may promote efficient HDR.…”
Section: Impaired Homology Asymmetrically Affects Drive Efficiencymentioning
confidence: 99%
“…The Cas9-RNA complex interrogates the target sites on the DNA via 3D diffusion, and recognises the complementary target site with the NGG PAM diffusion (Shibata et al, 2017). We used time-lapse microscopy to visualise the real-time dynamics of the dCas9-RNA complex for the labelling of telomeres of fixed nuclei in action (Fig.…”
Section: Researchmentioning
confidence: 99%